THE BRAIN AS THE CENTER OF THE HUMAN PERSONALITY - Eko Oktapiya Hadinata (SCHEMA (Journal of Psychological Research), 2018)
It is not uncommon for people to understand that humans are still very reductionist, especially those related to the center of human personality. So that, human discourse in various perspectives, causes a lot of confusion in the epistemology, whether the brain or heart is the center of the human personality. This study was carried out through a library research approach that refers to the perspective of Islamic psychology. The conclusion in this study is that the human brain is unique because of its dynamism as well as its mysteriousness which continues to evolve. In fact, the approach through quantum physics and uncertainty principle only has a small effect on the human brain. This study disagrees with Abdul Mujib and al-Ghazali that, having understanding and thinking and being responsible for the human personality is the heart, not the brain. Thus, this study is equivalent to Pare and Llines that, the nerve cells of the human brain are able to communicate with each other without being influenced by the senses, and Wahbah al-Zuhaili and Taufiq Pasiak that, when the brain is damaged then the human personality will also be damaged.